Voluntary self-regulation of as factor of competitive success of taekwondokas - Shagivaleeva, G. R.; Biserova, G. K.; Ldokova, G. M. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate and analyze volitional self-control correlation with the competitive performance in the 11-12 year old taekwondo groups. Methods and structure of the study. Sampled for the study were teenage taekwondokas (n=50) from Sports School No. 2 in Elabuga Municipal District, Republic of Tatarstan, split up into the actively competing Experimental Group (EG, n=25) including winners and runner-ups of the national and Republican competitions; and Reference Group (RG, n=25) of their non-competing although actively trained peers. The study was run using the following common research methods: theoretical analysis of the problem; and empirical test and survey methods including the T. Ehlers Motivation to Success Test; A.V. Zverkova and E.V. Aidman Volitional Self-Control Test method; C.D. Spielberger State-Trait Anxiety Inventory (with the state and trait anxiety tests in the Russian version adapted by Y.L. Khanin); plus a standard statistical test data processing toolkit.